(untitled) (Research, Society and Development, 2022)
For melon production to meet the standards required by the market, it is necessary to use technologies that make it possible to alleviate the effect of limiting factors on crop development. Irrigation, in addition to being one of these technologies, is identified as one of the alternatives for the socioeconomic development of semiarid regions. However, this must be properly managed in order to avoid problems of degradation of water and edaphic resources. Based on the above, the objective was to analyze the behavior of the melon crop under different soil water regimes. The experiment was carried out in a private area in the Baixo Acaraú Irrigation District, using melon seeds, var. inodorus, cv. F1 10/00 “yellow” type, irrigated with different irrigation depths. The seeds were planted in rows equidistant at 2 m, placing two seeds per emitter spaced approximately 12 cm apart, totaling 24 plants per row. The plants were irrigated with a localized drip system, with 2.3 L h-1 flow emitters, spaced 0.5 m apart. The amount of water applied was determined by the need to replace losses resulting from crop evapotranspiration (ETc). Postharvest shelf life (weight loss, brix and pulp firmness) was evaluated. It was found that the different blades provided in the cycle influenced the postharvest characteristics of fruit weight, brix and texture, however, the irrigation blades caused more effects on the weight and brix characteristics as it was increased, except for variable texture of the fruit.